SALIVARY GLAND TUMOURS: A REVIEW OF 91 CASES - Zaman, Samina; Majid, Sarosh; Chugtai, Omer; Hussain, Mahvish; Nasir, Mehreen (Journal of Ayub Medical College Abbottabad, 2014)
Background: Salivary gland tumours constitute heterogeneous group of tumours with different biological behaviour and account for 3% of all head and neck tumours. This study was conducted to study the clinico-pathological spectrum of salivary gland tumours. Methods: The study is a review of 91 cases of salivary gland tumours reported at Chugtai's Lahore Laboratory from 2009-2011. The clinical data of the patients was obtained from their respective files. Results: Age range of the patients was from 8-92 years. These tumours were slightly more common in females with female to male ratio of 1.1:1. Parotid gland (51.6%) was the commonest site for the occurrence followed by minor salivary glands (27.4%). Majority (58.2%) of them were benign. Of all the benign and malignant tumours pleomorphic adenoma (47.2%) was commonest tumour followed by adenoid cystic (17.5%) and mucoepidermoid tumours (16.4%). Conclusion: These tumours are more common in females with wide range of age distribution. Parotid gland is the most common site of involvement with pleomorphic adenoma being the commonest tumour type. Keywords: Salivary gland tumours, pleomorphic adenoma, adenoid cystic carcinoma, mucoepidermoid carcinoma